Exosome-Derived LncRNA TCONS_00072128 Mediated Osteogenic Differentiation and Inflammation by Caspase 8 Regulation - Yang, Yongchang; Miao, Li; Chang, Shuai; Zhang, Qiuli; Yu, Lijuan; He, Ping; Zhang, Yue; Fan, Weixiao; Liu, Jie; Hao, Xiaoke (Frontiers in Genetics, 2022)
Postmenopausal osteoporosis (PMOP) is a systemic metabolic bone disease in postmenopausal women. It has been known that long non-coding RNAs (lncRNAs) play a regulatory role in the progression of osteoporosis. However, the mechanism underlying the effects of exosome-derived lncRNA on regulating the occurrence and development of PMOP remains unclear. Exosomes in the serum of patients PMOP were collected and identified. RNA sequencing was performed to obtain the expression profile of exosome-derived lncRNAs in the serum of PMOP patients. RNA sequencing identified 26 differentially expressed lncRNAs from the exosomes between healthy people and PMOP patients. Among them, the expression of TCONS_00072128 was dramatically down-regulated. A co-location method was employed and searched its potential target gene caspase 8. TCONS_00072128 knockdown notably decreased the expression of caspase 8, while the osteogenic differentiation of BMSCs was also reduced. Reversely, TCONS_00072128 overexpression enhanced caspase 8 expression and osteogenic differentiation of BMSCs. Moreover, the continuous expression of caspase 8 regulated by TCONS_00072128 significantly activated inflammation pathways including NLRP3 signaling and NF-κB signaling. Simultaneously, RIPK1 which has emerged as a promising therapeutic target for the treatment of a wide range of human neurodegenerative, autoimmune, and inflammatory diseases, was also phosphorylated. The results of the present study suggested that exosome-derived lncRNA TCONS_00072128 could promote the progression of PMOP by regulating caspase 8. In addition, caspase 8 expression in BMSCs was possible to be a key regulator that balanced cell differentiation and inflammation activation.